Recent progress in cassava varietal improvement in Thailand - Rodjanaridpiched, C.; Limsila, Atchara; Supraharn, D.; Boonseng, O.; Poolsanguan, Piyawuth; Tiraporn, C.; Kawano, Kazuo (International Center for Tropical Agriculture, 1995)
Five cassava cultivars for industrial purposes, Rayong 3, Rayong 60, Sriracha 1, Rayong 90 and Kasetsart 50, were released during 1984-1992. New cultivars were simultaneously evaluated in research stations and farmers' fields in 53 locations during 1991 and 1992. Yields of each cultivar were regressed on mean yield of all cultivars in each location to detect the response of cultivars to 53 different yielding environments. New cultivars had higher HI and root DM content than the most important local cultivar, Rayong 1. Rayong 3, which had higher HI but lower total biological yield (TBY) than Rayong 1, yielded higher than Rayong 1 only in very high yielding environments. Rayong 60 and Rayong 90, which had higher HI and similar TBY to Rayong 1, yielded higher in high yielding environments, but in low yielding environments Rayong 60 yielded lower, while Rayong 90 yielded higher than Rayong 1. Kasetsart 50 and a promising clone, CMR25-105-112, which had higher HI and TBY, yielded higher than Rayong 1 in all environments. Results of effects of harvesting time (at 9 and 12 MAP) from nine experiments revealed that Rayong 60 yielded the highest at 9 MAP. In a different experiment it was found that Sriracha 1 was a good cultivar for late harvest (two years after planting). In contrast, late harvest resulted in high occurence of root rot in Rayong 60. Detailed studies on optimum season-of-planting and harvesting and on harvesting time of each cultivar is suggested for the future. Data on population means over 11 years of selection indicate that yield improvement in cassava is possible and could be achieved through selection for higher TBY and root DM content while maintaining high HI